CLINICAL STUDY ON TE-031 (A-56268) - WATANABE, KAZUYOSHI; IKEMOTO, HIDEO (CHEMOTHERAPY, 1988)
TE-031 (A-56268), a new macrolide antibiotic with a 14-membered ring, was developed by the Taisho Pharmaceutical Co. by replacing the hydroxyl group of the 6-position with a methoxyl group. Instability of conventional macrolides to acids and transfer of the drug into lung tissue and urine were improved. The present study was carried out to examine the clinical efficacy and side-effects of TE-031 in 15 patients with respiratoryinfection. Subjects were 8 males and 7 females, 56-78 years old (mean age 67.6). Diseases were acute bronchitis 9, bronchiectasis with infection 3, and chronic bronchitis 3. The dosages of TE-031 were 150mg twice daily for 7 patients, 200mg twice daily for 7, and 300mg twice daily for 1 patient, for 7-14 days (mean 9.8 days), with a total of 2.1-5.6g (mean total dosage 3.5g). Clinically, the effect was good in 11 cases and poor in 4, with an overall efficacy rate of 73.3%. Categorized by disease, TE-031 was good in 8 of 9 cases of acute bronchitis, good in 1 and poor in 2 of 3 cases of bronchiectasis with infection, and good in 2 and poor in 1 of 3 cases of chronic bronchitis. Sputum from 10 patients was cultured for bacteriological examination. H. influenzae, P. aeruginosa, K. pneumoniae and S. aureus were isolated from 3, 2, 1 and 1 cases, respectively. After administration, H. influenzae and S. aureus were eradicated in only 1 case each. No side-effects (such as drug eruption, fever, nausea, vomiting, and diarrhea) were observed, and laboratory values were normal before and after administration of TE-031.